2006
DOI: 10.1111/j.1538-7836.2006.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

CLOCK is involved in obesity-induced disordered fibrinolysis in ob/ob mice by regulating PAI-1 gene expression

Abstract: Summary. Background: An increased level of obesity-induced plasma plasminogen activator inhibitor-1 (PAI-1) is considered a risk factor for cardiovascular disease. Aim: The present study investigates whether the circadian clock component CLOCK is involved in obesity-induced PAI-1 elevation. Methods: We examined plasma PAI-1 and mRNA expression levels in tissues from leptin-deficient obese and diabetic ob/ob mice lacking functional CLOCK protein. Results: Our results demonstrated that plasma PAI-1 levels were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 43 publications
3
54
1
Order By: Relevance
“…For example, Clock mutant mice are obese and hyperphagic (107), although this phenotype may be modified by genetic background (110). Moreover, introgression of the Clock mutation into the ob/ob strain exacerbates obesity (111). In addition to causing metabolic disorders, both Clock mutant and Npas2 -/-mice display abnormalities in sleep architecture, so it will be critical to determine the cause-and-effect relationship between alterations in sleep and feeding in these models (112,113).…”
Section: Role Of the Circadian System In Energy Balance Metabolism mentioning
confidence: 99%
“…For example, Clock mutant mice are obese and hyperphagic (107), although this phenotype may be modified by genetic background (110). Moreover, introgression of the Clock mutation into the ob/ob strain exacerbates obesity (111). In addition to causing metabolic disorders, both Clock mutant and Npas2 -/-mice display abnormalities in sleep architecture, so it will be critical to determine the cause-and-effect relationship between alterations in sleep and feeding in these models (112,113).…”
Section: Role Of the Circadian System In Energy Balance Metabolism mentioning
confidence: 99%
“…Recently, Oishi et al reported that Clock-mutant mice carrying ICR exhibited less obesity (12), while Clock-mutant mice carrying C57BL / 6J exhibited more obesity with the ob mutation (13). This paper also suggests the different effect of Clock mutation on obesity.…”
Section: Effect Of Clock Mutation On Lipid Metabolismmentioning
confidence: 55%
“…Indeed, CLOCK protein is a positive regulator of PAI-1 mRNA expression (Oishi et al, 2006. That is, CLOCK/BMAL heterodimers transactivate the PAI-1 gene via the E-box element(s), and this activation is periodically suppressed by PER and CRY proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The results of microarray analyses using hepatic RNA isolated from bezafibrate-treated wild-type Clock mutant and PPAR␣-null mice revealed that 136 genes were transcriptionally regulated by PPAR␣ in a CLOCK-dependent manner in the mouse liver. Among them, PAI-1 was typical of genes with expression that exhibits circadian variation and has both PPRE and an E-box element in the promoter region (Chen et al, 2006;Oishi et al, 2006). We thus further focused on this gene to investigate the transcriptional interaction between PPAR␣ and CLOCK.…”
Section: Discussionmentioning
confidence: 99%